STEM-PjBL and creativity of science learning students in elementary schools - Rahayu, Annisa Septia; Maryani, Ika (Universitas Ahmad Dahlan, 2023)
Science learning is a lesson that studies nature and life. Science learning opens up opportunities for students to ask questions, develop new ideas, and build new skills, so this research aims to describe the implementation of STEM-PjBL, measure student creativity after implementing STEM-PjBL, and measure the influence of STEM-PjBL in science learning. This research uses a quantitative approach with the Pretest-Posttest Nonequivalent Control Group Design type. In this design, there are two groups: the experimental and the control groups. Data collection techniques use observation. The subjects used were 58 students, consisting of 28 as an experimental group and 30 as a control group. Data analysis techniques include a paired sample t-test and an independent sample t-test with a significance level of 5%. There is an increase in student creativity in the learning process. The results of the paired sample t-test show that there are significant differences in student creativity after the STEM-PjBL action in learning. The results of the independent sample t-test show that there are significant differences in STEM-PjBL actions in the learning process. STEM-PjBL has an influence on student creativity in the learning process.